PENGENDALIAN KUALITAS PRODUK GALON AIR MINERAL 19 L DENGAN PENDEKATAN SIX SIGMA - Arif, Afrizal; Wahid, Abdul (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
The problem faced by the company is the lack of product quality control that is used to reduce the number of defective products during the production process. Six sigma is a statistical-based quality improvement method, where the principle of this method is continuous improvement using statistical tools and problem solving tools. In this study, researchers applied the Six Sigma method which can be considered by the company as a product quality control method. In the measure stage through the calculation of the average product mismatch, it is known that the products that experience the largest defect rate of the company are black dirty, with an average value of 0.0285 and a sigma value of 3.2. In the next stage, the analyze phase through calculations using pareto diagrams, it is known that the dominant type of product defect is black dirty (65%) and the rest is dirty die head (2%) anamdel mouth (1%) bottom folded (1%). At the same stage through calculations using cause and effect diagrams, it is known that the factors that sequentially cause the product defects are 5 factors, namely human, material, method, machine and environment. The proposed improvements made by researchers into consideration in making improvements that can be useful to reduce the number of defective products or reject on gallon products.